Pertanggungjawaban Pidana Kader Kesehatan Posyandu dalam Promosi Susu Bayi Menurut Peraturan Perundang-Undangan di Indonesia - Christian Raka Joana; Frans Simangunsong (Media Hukum Indonesia (MHI), 2026)
The right of infants to receive exclusive breastfeeding is part of the state’s commitment to protecting child health. As an effort to support this policy, the government has established various legal provisions restricting the promotion of infant formula in order to prevent interference with breastfeeding practices. Nevertheless, in community health services, the involvement of Posyandu health cadres in activities related to infant formula promotion is still frequently found. This situation raises legal concerns regarding the possibility of criminal liability for those involved. This study aims to examine the forms of criminal liability that may be imposed on Posyandu health cadres involved in infant formula promotion under the Indonesian legal system. The research applies a normative legal method using statutory and conceptual approaches. The legal materials were collected through library research by examining legislation, scientific literature, and relevant legal doctrines. The findings indicate that health cadres may be held criminally liable if the elements of a criminal offense, as regulated under Article 430 of Law Number 17 of 2023 concerning Health, are fulfilled, particularly when the act is intentionally committed in a way that obstructs the implementation of exclusive breastfeeding. However, the imposition of criminal liability must still consider the element of fault, causality, and the possibility of legal grounds that may exclude criminal punishment.